Redescription and validation of Bothriechis supraciliaris (Serpentes: Viperidae) - Solórzano, Alejandro; Gómez, Luis D; Monge-Nájera, Julián; Crother, Brian I (Revista de Biología Tropical, 1998)
The populations of pitvipers from south western Costa Rica, have traditionally been identified as Bothriechis schlegelii (Berthold). However, in 1954 E. H. Taylor described one specimen from the area as a new subspecies, B. schlegelii supraciliaris. Werrnan returned supraciliaris to synonymy with schlegelii four decades latero However, morphometry and color pattern in a SW Costa Rica population (25 specimens) differ from those of specimens (N=57) from other parts of Costa Rica and from descriptions of South American specimens. Here ¡he epithet Bothriechis schlegelii supraciliaris Taylor 1954, is reestablished as a valid taxon and elevated to specific rank as B. supraciliaris stat.nov. It is closely related to B. schlegelii from which it differs by íts color patterns based on a uniforrn ground color with polymorphic dorsal designs, and its lower counts of ventral and caudal scales.